2011
DOI: 10.1104/pp.111.185215
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Induced Changes in Antifungal Phenolic Acids, Flavonoids, and Key Phenylpropanoid Pathway Genes during the Interaction between Miniature Roses and the Biotrophic Pathogen Podosphaera pannosa    

Abstract: Application of 3.6 mM silicon (Si+) to the rose (Rosa hybrida) cultivar Smart increased the concentration of antimicrobial phenolic acids and flavonoids in response to infection by rose powdery mildew (Podosphaera pannosa). Simultaneously, the expression of genes coding for key enzymes in the phenylpropanoid pathway (phenylalanine ammonia lyase, cinnamyl alcohol dehydrogenase, and chalcone synthase) was up-regulated. The increase in phenolic compounds correlated with a 46% reduction in disease severity compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 46 publications
8
76
0
3
Order By: Relevance
“…Al respecto, Shetty et al (2012), reportaron que la aplicación de 3.6 mM de Si (100 ppm) suministrado en solución nutritiva, reduce la severidad de P. pannosa hasta un 48.9 % dependiendo del genotipo del hospedante, de igual forma Datnoff et al (2006), demostraron que la aplicación de Si reduce significativamente la severidad de la cenicilla hasta en un 57 % en rosas de maceta. Estos reportes sugieren que la aplicación de Si desempeña un papel importante en la supresión de la cenicilla del rosal, lo cual puede ser explicado por un incremento en la concentración de compuestos fenólicos antimicrobianos y flavonoides en respuesta a la infección por P. pannosa (Shetty et al, 2011).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Al respecto, Shetty et al (2012), reportaron que la aplicación de 3.6 mM de Si (100 ppm) suministrado en solución nutritiva, reduce la severidad de P. pannosa hasta un 48.9 % dependiendo del genotipo del hospedante, de igual forma Datnoff et al (2006), demostraron que la aplicación de Si reduce significativamente la severidad de la cenicilla hasta en un 57 % en rosas de maceta. Estos reportes sugieren que la aplicación de Si desempeña un papel importante en la supresión de la cenicilla del rosal, lo cual puede ser explicado por un incremento en la concentración de compuestos fenólicos antimicrobianos y flavonoides en respuesta a la infección por P. pannosa (Shetty et al, 2011).…”
Section: Discussionunclassified
“…Regarding this, Shetty et al (2012) reported that applying 3.6 mM of Si (100 ppm) in a nutrient solution reduces the severity of de P. pannosa in up to 48.9 %, depending on the genotype of the host, as Datnoff et al (2006), demonstrated that applying Si reduces the severity of powdery mildew significantly, in up to 57 % in roses in pots. These reports suggest that the application of Si plays an important part in suppressing powdery mildew in rose bushes, which could be explained by an increase in the concentration of antimicrobial phenolic compounds and flavonoids in response to the infection with P. pannosa (Shetty et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These authors observed the complexation of phenolic compounds with silicon in the wall of epidermal cells so as to reduce and hamper the expansion of lesions and the disease intensity by making the cells more rigid, which was later confirmed by Rodrigues et al (2011). effect on disease reduction to the formation of both physical barriers, by deposition of Si (Sangster et al, 2001;Kim et al, 2002;Pozza et al, 2004;Carré-Missio et al, 2012b), and chemical barriers such as defense enzymes (Cherif et al, 1994;Fauteux et al, 2005;Cai et al, 2008;Shetty et al, 2011;Polanco et al, 2012). The joint action of these barriers in disease control in plants fertilized with Si was observed by Cai et al (2008) and Resende et al (2013).…”
Section: Modes Of Silicon Action In Plant Disease Controlmentioning
confidence: 99%
“…Other crops such as strawberry, soybean, tomato and rose also showed promising results in reducing disease with Si application (Kanto et al, 2006;Carré-Missio et al, 2010;Lima et al, 2010;Ghareeb et al, 2011;Shetty et al, 2011). Conidia of Sphaerotheca aphanis var.…”
Section: Silicon In Disease Control In Dicotyledonsmentioning
confidence: 99%
See 1 more Smart Citation